Fragment N2, a caspase‐3‐generated RasGAP fragment, inhibits breast cancer metastatic progression. Issue 1 (4th March 2014) - Barras, David; Lorusso, Girieca; Lhermitte, Benoît; Viertl, David; Rüegg, Curzio; Widmann, Christian
Abstract : The p120 RasGAP protein negatively regulates Ras via its GAP domain. RasGAP carries several other domains that modulate several signaling molecules such as Rho. RasGAP is also a caspase‐3 substrate. One of the caspase‐3‐generated RasGAP fragments, corresponding to amino acids 158–455 and called fragment N2, was previously reported to specifically sensitize cancer cells to death induced by various anticancer agents. Here, we show that fragment N2 inhibits migration in vitro and that it impairs metastatic progression of breast cancer to the lung. Hence, stress‐activated caspase‐3 might contribute to the suppression of metastasis through the generation of fragment N2. These results indicate that the activity borne by fragment N2 has a potential therapeutic relevance to counteract the metastatic process. Abstract : What's new? Cancer's ability to spread all over the body is what makes it most deadly, but metastasis remains a tough problem to solve. Researchers are scrutinizing the molecular changes that allow a cancer cell to break away from a tumor and colonize another part of the body, and one key player is the Ras protein family, which in turn can be stifled by proteins called RasGAPs. In this paper, the authors investigated a caspase‐3‐generated fragment of one of the RasGAPs (p120 RasGAP), already known to sensitize cancer cells to anti‐cancer drugs. They found that this fragment, called N2, can also halt metastasis. These results suggest that activation of caspase‐3, which creates the fragment, could help kill off tumors and prevent metastasis.